IMPROVEMENT OF POROUS GRAPHITE PLATE FOR PEM FUEL CELL BY ORGANO-IMPREGNANTS - Akhtar, M. N.; Qureshi, A. H.; Qureshi, A. H. (The Nucleus, 2020)
Porous graphite plates with improved properties for proton exchange membrane (PEM) fuel cells were fabricated from organo-impregnant materials such as styrene, epoxy resin and cyanoacrylate. The results revealed that porosity of porous graphite plate has been completely removed. However, the graphite plate impregnated with styrene was not thermally stable around the temperatures 80-100oC. The impregnated plates were also characterized to determine the properties such as density, mechanical properties, thermal stability and electrical conductivity. Study revealed that the graphite plates impregnated with cyanoacrylate was more suitable for PEM fuel cell applications.